โครงการวิจัยเรื่องการพัฒนาต้นแบบพวงหรีดเพื่อสิ่งแวดล้อมโดยการมีส่วนร่วมของชุมชน - งามสระคู, รุจิราภา (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
The Development of Environmental Friendly Wreath Prototypes by Community Participation is a cooperative action research. The objective to Design and Develop prototype of wreaths from wasted materials and convey the knowledge of the development of wreath products from waste materials to students and communities. And study consumer’s satisfaction in designing and developing a wreath prototype for the environment by Community Participation. To bring local wisdom and culture to add value to creative products in the community for environmental conservation and community empowerment. The Principles of Composition is an important tool in the design of eco-friendly products by creating four new wreath prototypes. By using waste material such as coffee packs, pieces of paper, plastic bottles to make a wreath to design with the community. And transfer the knowledge to members of the community network to given an idea for community to invent new conceptual wreaths for the ceremony to sell for incomes, and to solve the garbage problem in the communities by recycling. There were 4 communities participating in this project; Praisanee Ram-Intra 65 Community of Bang Khen District in Bangkok, Dow Thong Community of Don Muang District in Bangkok, Patcharapa Community of Lak Si District in Bangkok, and Ban Fah Rangsit Community in Pathumthani Province. The research found that 4 prototypes of wreaths are derived from the process of converting waste into new products of higher quality and value And beautiful new concept wreath Natural colors are used. Aesthetic value completely. The important thing is to stimulate the consciousness of environmental conservation of the community. Which together named the wreath. “Wreath to save the Earth” to represent the symbol as a new choice for conservator. The results of the survey on the satisfaction of the wreath prototype products for the environment showed that the use of waste materials to exploit. Price Design And useful side Consumers are satisfied in all aspects at all levels.